Synthesis, Crystal Structure and Antimicrobial Activity of A Linear Trinuclear Nickel(II) Complex with Schiff Base Ligand - Cui-Lin Zhang; Xiao-Yang Qiu; Shu-Juan Liu (Acta Chimica Slovenica, 2019)
A new linear trinuclear Schiff base nickel(II) complex, [Ni{NiL(μ2-η1:η1-OAc)(OH2)}2]·H2O, where L is the dianionic form of N,N’-bis(5-chloro-2-hydroxybenzylidene)-1,3-propanediamine (H2L), was synthesized and characterized by elemental analyses, IR spectroscopy, and X-ray single-crystal determination. There are three bridges across the Ni-Ni atom pairs, involving two phenolate O atoms of a Schiff base ligand, and an O–C–O moiety of a μ2-η1:η1-OAc group. The Ni atoms have octahedral coordination. The acetate bridges linking the central and terminal nickel atoms are mutually trans. The adjacent Ni∙∙∙Ni distances are 3.047(1) Å. The complex was evaluated for its antibacterial (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa) and antifungal (Candida albicans and Aspergillus niger) activities by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method.